2011
DOI: 10.1007/s00330-011-2179-2
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous local ablation of unifocal subclinical breast cancer: clinical experience and preliminary results of cryotherapy

Abstract: Objectives To assess the ablative effectiveness, the oncological and cosmetic efficacy of image-guided percutaneous cryoablation in the treatment of single breast nodules with subclinical dimensions after identification with ultrasonography (US), mammography, magnetic resonance (MRI) and characterization by vacuum assisted biopsy. Materials Fifteen women with a mean age of 73±5 years (range 64-82 years) and lesion diameter of 8±4 mm were undergoing cryotherapy technology with a single probe under US-guidance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…108,111,114,132,135 Reported complications following the percutaneous procedures included bruising, skin burns and necrosis, 91,103,113,114,136 as well as similar complications to those expected from open surgery, including seromas 91,115,143 and haematomas. 105,115,125,136,140,141,143 The lack of adequate follow-up data reported within these studies makes it difficult to assess the recurrence risk, with only one study of RFA reporting three local recurrences in 21 patients with invasive breast cancer at 60 months of follow up. 101 Long-term follow up is difficult as the majority of studies conducted are window studies, with percutaneous ablation followed by standard surgical excision.…”
Section: Minimally Invasive Percutaneous Surgerymentioning
confidence: 95%
“…108,111,114,132,135 Reported complications following the percutaneous procedures included bruising, skin burns and necrosis, 91,103,113,114,136 as well as similar complications to those expected from open surgery, including seromas 91,115,143 and haematomas. 105,115,125,136,140,141,143 The lack of adequate follow-up data reported within these studies makes it difficult to assess the recurrence risk, with only one study of RFA reporting three local recurrences in 21 patients with invasive breast cancer at 60 months of follow up. 101 Long-term follow up is difficult as the majority of studies conducted are window studies, with percutaneous ablation followed by standard surgical excision.…”
Section: Minimally Invasive Percutaneous Surgerymentioning
confidence: 95%
“…In 2008, van der Ploeg et al [9] published the first case of MRI-guided breast RFA in 3 patients with invasive ductal carcinoma and no artifacts around the needle electrode [9,10]. Although the iceball produced during cryoablation reduces the visibility in deeper tissues, it is much more regular, definite, and symmetric, allowing an easier comparison between the margins of the lesion and the ablation volume [11]. All RFAs were performed successfully, with no tissue impedance rising above 20 Ω from baseline during the procedure, independent of the breast composition pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The greatest success in complete cell death has occurred in tumors o2 cm in diameter, and especially those that are 1.5 cm or smaller, without extensive ductal carcinoma in situ. 3,4 Patients with tumors 42 cm are generally considered poor candidates owing to the presence of sonographically occult tumor extension.…”
Section: Cryoablationmentioning
confidence: 99%
“…7 The most recent cryoablation clinical trial among 15 women with lesions 4-12 mm in diameter reported that MRI was accurate in detecting the solitary case of 3-mm residual tumor, considered owing to suboptimal eccentric probe positioning during cryoablation. 1 Cell death is achieved by freezing tissue with a percutaneous 3-mm probe, typically with ultrasound guidance (Fig. 1A and B).…”
Section: Cryoablationmentioning
confidence: 99%
See 1 more Smart Citation